A sermon delivered at the opening of the Barmen/Belhar Consultation at Belhar, 18 October 2004 - Buys, J (Nederduitse Gereformeerde Teologiese Tydskrif, 2006)
One of the profound experiences of those who attended the 24th General Council Meeting of the WARC in Accra Ghana in July August this year, was a visit to the slave dungeons near the city. These formed part of a series of castles or forts built on the West African Coast that served as slave trading posts. Central to these castles were the churches attached to them that served as places of worship. However, while God was being worship on the upper floors, slaves were suffering and dying in the dungeons underneath. Those who survived incarceration in the dungeons were then taken to the ‘door of no return’ from where they were transported by ship to foreign shores. Many more died at sea while the remainder would suffer the hardship of slavery in new lands.